Antibacterial efficacy of fruit extracts from three mangrove species: Rhizophora mucronata, Sonneratia alba, and Sonneratia caseolaris against multidrug-resistant (MDR) isolates derived from clinical specimens - Muhmmad Evy Prastiyanto; Fandhi Adi Wardoyo (Journal of HerbMed Pharmacology)
Introduction: The emergence of multidrug-resistant (MDR) bacteria poses a significant challenge to public health, necessitating the exploration of alternative antimicrobial agents. This study investigates the antibacterial activity of fruit extracts from Rhizophora mucronata, Sonneratia alba, and Sonneratia caseolaris against MDR isolates derived from clinical specimens. Methods: Antibacterial activity was assessed against multiple multidrug-resistant bacterial strains, such as methicillin-resistant Staphylococcus aureus (A) strain sa1, vancomycin-resistant Enterococcus (VRE) strain ef1, carbapenem-resistant Pseudomonas aeruginosa (CRPAMRS) strain ps1, and extended-spectrum beta-lactamase (ESBL) Escherichia coli strain ec1. The antibacterial efficacy was determined using an agar-based well diffusion test to ascertain the zone of inhibition. Microdilution was assessed to ascertain the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. Standard procedures were used to screen for plant phytochemicals (terpenoid, alkaloid, flavonoid, tannin, and saponin). Results: An ethanol extract of mangrove fruit exhibited antibacterial activity against MRSA, VRE, CRPA, and ESBL-Escherichia coli, producing an inhibitory zone diameter of 3-24 mm at 10 and 20 mg/mL, with MIC and MBC values exceeding 20 mg/mL. Specifically, Sonneratia alba was effective against MRSA and VRE with MIC and MBC values ≥10 mg/mL. Sonneratia caseolaris was effective against CRPA and ESBL-Escherichia coli with MIC and MBC values ≥5 mg/mL Phytochemical identification results showed the presence of terpenoids, alkaloids, flavonoids, tannins, and saponins in all three extracts. Conclusion: The fruit extracts examined have antibacterial activity against MDR isolates. Additional studies are required to isolate and characterize the specific bioactive substances that generate these effects.